Reality Individual Counseling For Victims Of Verbal Sexual Harassment - Meiliawati, Meiliawati; Sulistianingsih, Sulistianingsih; Marliani, Lina (Worldwide Research Publishing, 2023)
Students who are bullied are often shunned and isolated, so that victims of sexual harassment tend to adopt negative coping strategies, such as skipping class, violating school rules, being individual, then falling into promiscuity to avoid sexual harassment. Sexual harassment that is considered normal will unconsciously cause negative views on child victims, including depression, lazy learning, frequent truancy, neglect and rejection by the surrounding environment. In addition, victims did not respond or take a firm stance against sexual harassment. This type of research is qualitative research using case study research methods. According to Nawawi, case study data can be obtained from all parties concerned. In other words, the data in this study was collected from various sources. Based on an analysis of the results of research conducted by researchers at SMP Negeri 1 Karangsembung regarding the implementation of individual counseling services to deal with victims of verbal sexual harassment, students at SMP Negeri 1 Karangsembung Cirebon, there are forms of verbal sexual harassment that are mild, moderate, even severe. The mild form of harassment is often teased by friends, while the moderate form of harassment is whistling and the heavy form is mocking animals. Occurred for 4 consecutive months experienced by victims of ZAB, CA and PAR. So that they experience mild harassment, namely being insecure with their peers, and moderate harassment becomes negative thinking and lack of confidence, while severe harassment is experiencing mental trauma and then the solution for the counseling teacher is to carry out individual counseling with reality techniques. Conclusion, The changes seen after individual counseling with reality techniques for victims of verbal sexual harassment at Karangsembung State Middle School,. Although individual counseling services with reality techniques carried out by researchers are good services for students. It is proven that there are changes that occur for students in class. Although these changes have not been significant for victims of verbal sexual harassment, dynamic changes have occurred. Previously, ZAB, CA and PAR were students who were traumatized by acts of verbal sexual harassment against them. ZAB, CA and PAR are now able to recover from their trauma and are willing to hang out with their friends. Even in a learning class, they have started to be active and can follow the lesson well.